1986
DOI: 10.1002/anie.198607201
|View full text |Cite
|
Sign up to set email alerts
|

Bridged [14]Annulenes with a Phenanthrene‐Perimeter: syn‐1,6:7,12‐Bismethano[14]annulene

Abstract: The idea of transforming a classical arene, by “bridging,” into a [4n+2]annulene has been further extended to the phenanthrenes. The spectroscopic data and structural parameters for the title compound 1 reveal it to be a borderline case, with respect to its π‐electron structure, for an aromatic molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The syn 115 and anti 116 conformers of bridged annulene[14] derivatives differ much in aromaticity. Application of HOMA and its components to the perimeter bond lengths allowed us to look at it in a more subtle way.…”
Section: E Nonbenzenoid Alternant Hydrocarbons and Their Heteroanaloguesmentioning
confidence: 99%
“…The syn 115 and anti 116 conformers of bridged annulene[14] derivatives differ much in aromaticity. Application of HOMA and its components to the perimeter bond lengths allowed us to look at it in a more subtle way.…”
Section: E Nonbenzenoid Alternant Hydrocarbons and Their Heteroanaloguesmentioning
confidence: 99%
“…The syn-bismethano [14]annulene 135, prepared in 1986 by the Vogel group, 123 has all of the necessary features for bis-addition of an alkynyl dienophile that would provide the essential progenitor for 137. However, while the authors found that addition of DCA does take place, it is only to the bay region "diene" to give 136, and not across the bridge centers as is required for the ultimate preparation of 137.…”
Section: By Employing Other Bicyclo[410]heptenesmentioning
confidence: 99%
“…Here it should be noted that the ring openings, e.g., with PhSH and Bu 3 SnH, give aryl-substituted product as major product with an orientation precisely the opposite to that of classical thermal chemistry. Despite these observations, Okazaki and co-workers had earlier shown that the addition of iodine and thiocyanogen to 2 under photochemical conditions leads to 1,6-disubstituted cycloheptatrienes in good yields such that the reaction has provided for much use of 2 in synthesis. ,, In these reactions radical addition is thought to take place across the bridge bond to give a 1,6-disubstituted norcaradiene that opens to the preferred valence bond isomer, but smaller amounts (to ca. 30%) of α, o- disubstituted toluenes are still formed.…”
Section: A With Electrophiles Nucleophiles and Radicalsmentioning
confidence: 99%
“…By that time in 1989, we and others had attempted the synthesis of the benzenoid nucleus strained by double cyclopropa ring fusions as illustrated by 10–13 . Biscyclopropa–fused aromatics such as 10 had been prepared relatively easily, but the efforts to impose markedly more strain by fusing two three‐membered rings onto one naphthenoid ring failed.…”
Section: Methodsmentioning
confidence: 99%